2014
DOI: 10.1111/ggi.12331
|View full text |Cite
|
Sign up to set email alerts
|

Presence of and correction for interviewer error on an instrument assessing cognitive function of older adults

Abstract: Investigators using the SPMSQ, and potentially, other instruments, for assessing cognitive function in surveys of older adults and using face-to-face interviews for data collection should be cognizant of the sensitivity of such instruments to interviewer error. Intensive training of interviewers to standardize instrument administration as well as assessment for interviewer error and its correction, using appropriate statistical models, such as multilevel models, is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…due to dementia, speaking difficulties). The proxy interviews were excluded here because variables including social network, depression, and cognition were not assessed through the proxies (Chan et al, 2011;Malhotra et al, 2015). Another major source of missing data was the record of body mass index (BMI).…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…due to dementia, speaking difficulties). The proxy interviews were excluded here because variables including social network, depression, and cognition were not assessed through the proxies (Chan et al, 2011;Malhotra et al, 2015). Another major source of missing data was the record of body mass index (BMI).…”
Section: Participantsmentioning
confidence: 99%
“…Health surveys of older adults conducted in faceto-face interviews, particularly instruments assessing cognitive function, are subject to interviewer error (Malhotra et al, 2015). Interviewer error is a type of measurement error.…”
Section: Main Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been used in community samples to identify persons 65 years and older with cognitive impairment and clinically diagnosed Alzheimer's disease ( Albert et al, 1991 ). Moreover, studies have used this scale as a measure of global cognition ( Sachs-Ericsson and Blazer, 2005 , Sawyer et al, 2008 ) and have validated the sensitivity of this instrument for interviewer error when assessing cognitive functioning among older adults ( Malhotra et al, 2015 ). The measure tests a participant’s orientation (i.e., identifying today’s date and day of the week), knowledge of current and past affairs (i.e., naming the current and former Presidents of the United States), and working memory (i.e., using the serial 3s subtraction test).…”
Section: Methodsmentioning
confidence: 99%
“…However, it is demonstrated that trained clinicians can accurately judge self and/or informant reports on ADLs [ 29 ]. Nonetheless, since the most reported cause of limitations in ADLs is ‘old age’ [ 30 , 31 ], it is important that clinicians carefully explore the reasons of limitations by using probes such as ‘How do you/does (s)he performs this activity?’ or ‘What causes the need for help to perform this activity?’.…”
Section: Discussionmentioning
confidence: 99%